Modification of plant cell walls with hydroxycinnamic acids by BAHD acyltransferases - Chandrakanth, Niharika Nonavinakere; Zhang, Chengcheng; Freeman, Jackie; de Souza, Wagner Rodrigo; Bartley, Laura E.; Mitchell, Rowan A.C. (Frontiers in Plant Science, 2023)
In the last decade it has become clear that enzymes in the “BAHD” family of acyl-CoA transferases play important roles in the addition of phenolic acids to form ester-linked moieties on cell wall polymers. We focus here on the addition of two such phenolics—the hydroxycinnamates, ferulate and p-coumarate—to two cell wall polymers, glucuronoarabinoxylan and to lignin. The resulting ester-linked feruloyl and p-coumaroyl moities are key features of the cell walls of grasses and other commelinid monocots. The capacity of ferulate to participate in radical oxidative coupling means that its addition to glucuronoarabinoxylan or to lignin has profound implications for the properties of the cell wall – allowing respectively oxidative crosslinking to glucuronoarabinoxylan chains or introducing ester bonds into lignin polymers. A subclade of ~10 BAHD genes in grasses is now known to (1) contain genes strongly implicated in addition of p-coumarate or ferulate to glucuronoarabinoxylan (2) encode enzymes that add p-coumarate or ferulate to lignin precursors. Here, we review the evidence for functions of these genes and the biotechnological applications of manipulating them, discuss our understanding of mechanisms involved, and highlight outstanding questions for future research.